Ответ:
{ 7х - 3у = 13
{ х - 2у = 5
Выразим х через у ↓
{ х = 2у + 5
Составим уравнение ↓
7(2у + 5) - 3у = 13
14у + 35 - 3у = 13
14у - 3у = 13 - 35
11у = - 22
у = - 2
Подставим значение у в любое уравнение ↓
х - 2 * (- 2) = 5
х + 4 = 5
х = 5 - 4
х = 1
Ответ : (1; - 2)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
{ 7х - 3у = 13
{ х - 2у = 5
Выразим х через у ↓
{ 7х - 3у = 13
{ х = 2у + 5
Составим уравнение ↓
7(2у + 5) - 3у = 13
14у + 35 - 3у = 13
14у - 3у = 13 - 35
11у = - 22
у = - 2
Подставим значение у в любое уравнение ↓
х - 2 * (- 2) = 5
х + 4 = 5
х = 5 - 4
х = 1
Ответ : (1; - 2)